Differential linear brain growth patterns in preterm neonates based on birth gestational age and steroid exposure: A retrospective chart review - Medha Goyal; Meagan Quigley; Sourabh Dutta; Nina Stein; Ipsita Goswami (PLoS ONE, 2025)
Objective To assess the differences in brain growth between extreme preterm [EP](22–28wks gestation age [GA]) and very preterm infants [VP](28+1–32wks GA) using two-dimensional cranial ultrasound(cUS) at term equivalence. Study design Retrospective study of neonates born at GA of ≤ 32 weeks between 1st January 2019 and 31st December 2022, without major parenchymal brain injury. Results 326 neonates, with 207 EP and 119 VP, were enrolled. EP infants compared to VP had significantly lower biparietal diameter [7.7vs7.9 cm, p = 0.003], corpus-callosum length [3.8vs4.1 cm, p < 0.001], corpus-callosum-fastigial distance [4.5vs4.8 cm, p = 0.004] and cerebellar-vermis height [2.1vs2.2 cm, p = 0.002]. Cumulative postnatal steroid exposure had no significant association with brain metrics; however, exposure to antenatal steroids was negatively associated with corpus-callosum length [β = −0.38 (−0.58 to −0.7),p = 0.0003] and pons anteroposterior depth [β = −0.36 (−0.47 to −0.25),p < 0.0001] despite adjustments for clinically important risk factors. Conclusion Preterm infants born ≤ 28 weeks GA have significantly smaller dimensions of major white matter tracts than preterm infants born 28–32 weeks GA at term equivalence. Exposure to antenatal steroids negatively impacts corpus-callosum length and pons anteroposterior depth.